2016
DOI: 10.1097/sla.0000000000001565
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Vagus Nerve-preserving Distal Gastrectomy Versus Conventional Distal Gastrectomy for Postoperative Quality of Life in Early Stage Gastric Cancer Patients

Abstract: Early gastric cancer patients undergoing VPG reported significantly less diarrhea and appetite loss at 12 months postsurgery compared with those undergoing CG, with no differences in long-term clinical outcomes. VPG may improve the quality of life after gastrectomy in early gastric cancer patients compared with CG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Furthermore, delayed gastric emptying, endoscopic findings a year after LPPG, such as the presence of residual food, remnant gastritis, and the incidence of gallstone formation, were not different between the groups, although previous studies have reported that the preservation of the vagal nerve maintains gastrointestinal motility and prevents postoperative gallstones [11,12]. In terms of patient symptoms, Kim et al have reported that preserving the vagal nerve attenuates the occurrence of diarrhea and appetite loss after distal gastrectomy [14]. Because the present study was retrospective and observational, the postoperative symptoms of our patients could not be precisely evaluated.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Furthermore, delayed gastric emptying, endoscopic findings a year after LPPG, such as the presence of residual food, remnant gastritis, and the incidence of gallstone formation, were not different between the groups, although previous studies have reported that the preservation of the vagal nerve maintains gastrointestinal motility and prevents postoperative gallstones [11,12]. In terms of patient symptoms, Kim et al have reported that preserving the vagal nerve attenuates the occurrence of diarrhea and appetite loss after distal gastrectomy [14]. Because the present study was retrospective and observational, the postoperative symptoms of our patients could not be precisely evaluated.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, LPPG has become one of the surgical modalities used for early gastric cancer to reduce invasion [8,17,[25][26][27]. However, the clinical significance of the CBVN preservation, which has an advantage in distal gastrectomy, has not been clear in PPG [14]. In the present study, we retrospectively analyzed the short-and long-term outcomes of the CBVN preservation in LPPG.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A recently published randomised controlled trial of vagus preserving versus conventional distal gastrectomy, including 163 patients, demonstrated reduced diarrhoea and appetite loss at 12 months post-surgery (16). In our experience, it is possible to preserve the posterior vagus nerve while performing a PTG with adequate oncological clearance for a T1 signet ring adenocarcinoma.…”
Section: Editorialmentioning
confidence: 80%
“…The benefits of VNPG are seen in the superior recovery of body weight and reduction in the incidence of gallstone development. 35 A randomized controlled trial 37 in South Korea comparing vagus nerve-preserving distal gastrectomy to conventional gastrectomy showed significantly less diarrhea and appetite loss at 12 months with vagus nerve preservation. There was no difference in the long-term clinical complications, recurrence, and survival.…”
Section: Discussionmentioning
confidence: 99%